Production of spinach under variable water supply - Fazlil Ilahi, Wan Fazilah; Saroni, Nurul Sahirah; Che'ya, Nik Norasma (Malaysian Society of Agricultural Engineers, 2019)
The effects of a variable water supply on the growth and yield of spinach grown in cocopeat medium was examined in a field experiment. Three irrigation treatments; (T1) common practice (T2) crop water requirement; and (T3) time scheduling were monitored through the season from transplanting to harvest, 28 days (from January and February 2018) after planting located in a shade house. For T1, spinach was irrigated 2 times per day until the medium surface is wet. An estimated value of crop evapotranspiration (ETc) was determined for spinach during this period in T2, giving a water requirement of 3.72 mm/day (for January 2017) and 4.04 mm/day (for February 2017). The irrigation interval was three days and scheduled water was given based on the ETc value in T2 for T3. There were no significance response to the irrigation treatments for plant height, number of leaves, canopy diameter and leaf length despite differences in biomass production measured. Plant fresh weight and root length density was more sensitive in T3. The insignificant difference was hypothesized to be contributed by that cocopeat medium used in this study that had provided satisfactory available water for the spinach growth regardless different amount of irrigation water applied.